Association between body shape index and coronary heart disease in individuals over 20 years old with obese - Huabin He; Yang Chen; Yanhui Liao; Longlong Hu; Hao Qin; Renqiang Yang (BMC, 2024)
Abstract Background While body mass index (BMI) defines obesity as a well-established risk factor for cardiovascular disease, the paradoxical theory of BMI suggests that obesity may indeed have a favorable impact on the prognosis of cardiovascular disease. Therefore, this study aims to assess the correlation between body shape index (ABSI), which is a novel measure of obesity, and coronary heart disease (CHD) among obese individuals in the United States. Methods The data from the National Health and Nutrition Examination Survey (NHANES) were evaluated by us for 5046 patients. We assessed the exposure variable ABSI, which includes waist circumference (WC), height, and BMI. The outcome variable was CHD. Results The cross-sectional study included a total of 5046 obese adults aged over 20 years, with an average age (standard deviation: SD) of 49.86 (16.24) years and a male proportion of 44.57%.The odds ratio (OR) values for CHD in Model 1, Model 2, 3 were found to be 2.45 (95%CI: 2.12, 2.83), 1.53 (95%CI:1.30, 1.81) and 1.31 (95%CI:1.09, 1.56) per SD increase in ABSI, respectively. In the fully adjusted model, we designated participants in the T1 group as the reference group. Our findings indicate a significant increase in the prevalence of CHD (OR:1.82, 95%CI: 1.07-3.10) only within the T3 group. Although there is an increased prevalence of CHD (OR:1.32, 95%CI: 0.77-2.29) in the T2 group, no statistically significant difference was observed. Conclusions The increase in ABSI is strongly associated with the rise in CHD prevalence among obese individuals in the United States.